Microbacterium invictum sp. nov., isolated from homemade compost - Vaz-Moreira, Ivone (2011)
Strain DC-200T was isolated from homemade compost produced from kitchen refuse and characterized using a polyphasic approach. The isolate was a Gram-positive motile short rod, facultatively aerobic, catalase-positive and oxidase-negative, and was able to grow at 10–37 6C, pH 6.0–9.5 and with up to 5% of NaCl. The peptidoglycan was of the type B1 alpha and the muramic acid residues were glycolylated. The major fatty acids were anteiso-C15 : 0 and anteiso- C17 : 0. The predominant respiratory menaquinones were MK-11 and MK-12. The G+C content of the genomic DNA was 70 mol%. Based on the analysis of the 16S rRNA gene sequence, the closest phylogenetic neighbours of strain DC-200T were Microbacterium lacus A5E-52T (98.7 %) and Microbacterium aoyamense KV-492T (98.2 %). The phenetic characterization of the isolate supports its inclusion within the genus Microbacterium; however, its distinctive phenotypic features and the results from the 16S rRNA gene sequence analysis and the DNA–DNA hybridization study suggest that the isolate represents a novel species. The name Microbacterium invictum sp. nov. is proposed. The type strain is DC-200T (5DSM 19600T5LMG 24557T).